Handbook of petroleum product analysis - Speight, James G. (Wiley, 2015)
Introduces the reader to the production of the products in a refinery Introduces the reader to the types of test methods applied to petroleum products, including the need for specifications Provides detailed explanations for accurately analyzing and characterizing modern petroleum products Rewritten to include new and evolving test methods Updates on the evolving test methods and new test methods as well as the various environmental regulations are presented.
Includes index.
Keywords: Petroleum products -- Analysis.; elektronické knihy; electronic books